Fluxo de coerência quântica para um qubit evoluindo sobre a ação de canais quânticos - Pozzobom, Mauro Buemo (2016)
Quantum Coherence (QC) has a fundamental role in Quantum Mechanics (QM). It has been studied since the emergence of QM. However, this quantum feature is easily destroyed when a physical system interacts with the environment. Also, recently the quantum coherence has been highlighted because of the possibility of using its as a resource in the Quantum Information Science (QIS). In this work we study the QC flow of a qubit (two-level system) interacting with the environment modeled by quantum channels of noise that are very common in QIS. These channels represent some physical systems and are widely used for error correction studies. We calculate the QC by the l1-norm, doing this for the different channels seeking to relate it to the entanglement, which is also another key topic in QM. We note that in the amplitude damping channel the total QC is equal to the sum of the local and non-local parts and that the non-local part is equivalent to entanglement. For the phase damping channel, entanglement does not cover all non-local QC. Here there is a gap between them that may depend on the time and on the initial state. Besides, for the bit, phase, and bit phase flip channels the possibility and the conditions for invariance of QC are considered. Also, we notice that for the depolarizing channel we can use the qubit as a catalyst for the creation of non-local QC and entanglement. We, as well, observed that even initial states incoherent can lead to transient quantum coherence between system and environment. We also showed that the emergence of entanglement does not necessarily imply the destruction of QC. Furthermore, we investigated whether QC is lost or changed into other types of correlations and besides which initial conditions allow making quantum coherence robust to decoherence.